DISTRIBUSI DAN BIOAKUMULASI KROM (Cr) PADA KERANG AIR TAWAR (Anodonta woodiana Lea, 1834) DAN EFEKNYA PADA KERUSAKAN DNA GENOM SEL INSANG - , I GEDE ANGGA PRAMUDITA, Dr. rer. nat. Andhika Puspito Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chromium (Cr) is one of metals which are toxic to organisms at elevated concentration. In freshwater ecosystem, Cr concentration can be increased due to discharge of chromium-containing wastewater coming from leather tanning and electroplating industries. Mussels are known to accumulate metals in their body. The objectives of this research were to study distribution and bioaccumulation of Cr in the freshwater mussel Anodonta woodiana, and its effect on genomic cells DNA damage of gills. Mussels are exposed to Cr water (25 Î¼g L -1 ) for 24 days, followed by 12 days of depuration. On day 0, 1, 6, 12, 24 (exposure), and day 30 and 36 (depuration), 3 mussels are sampled and dissected to obtain gills, mantle, intestine, foot, kidney, and adductors. Hemolymph (HML) was withdrawn from the posterior adductor and extra pallial fluids (EPF) was withdrawn between mantle and inner shell. Bioaccumulation of Cr in all organs, HML, and EPF was determined by using Atomic Absorbance Spectrophotometer (AAS). Analysis of the genomic cells DNA damage of gills was qualitatively determined by using gel agarose electrophoresis. The data of bioaccumulation analyzed with Statictica 8 program, ANOVA and T-test (Î±= 0.05). The results showed that Cr concentrations increased in all organs within 24 days of exposure, the highest level being in kidney, followed by intestine. For HML and EPF, Cr concentrations were increased during early exposure and back to normalize near end of exposure. During exposure, Cr induced the genomic cells DNA damage of gills and back to normal at day 12 of depuration.